2002
DOI: 10.1067/mtc.2002.122298
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of ground-glass opacity on high-resolution computed tomography in clinical T1 N0 M0 adenocarcinoma of the lung: A predictor of lymph node metastasis

Abstract: In patients with clinical T1 N0 M0 adenocarcinoma, the proportion of ground-glass opacity area on thin-section computed tomography scans was a strong predictor for tumor aggressiveness and thus could be a useful index for planning limited surgical resection for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
138
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 19 publications
(25 reference statements)
9
138
0
Order By: Relevance
“…As reported elsewhere, TDR (quantitatively estimated GGO areas) is defined as the ratio of tumor area on mediastinal window images to that on lung window images [4,5]. According to previous studies, the proportion of GGO in a partsolid nodule and the aggressiveness of lung adenocarcinomas have inverse correlation (large area of GGO indicates a good prognosis) [6,7]. On imaging-pathological correlation study, TDR at HRCT corresponds to the extent of BAC component area [5], and thus seems to be linked to low aggressiveness of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…As reported elsewhere, TDR (quantitatively estimated GGO areas) is defined as the ratio of tumor area on mediastinal window images to that on lung window images [4,5]. According to previous studies, the proportion of GGO in a partsolid nodule and the aggressiveness of lung adenocarcinomas have inverse correlation (large area of GGO indicates a good prognosis) [6,7]. On imaging-pathological correlation study, TDR at HRCT corresponds to the extent of BAC component area [5], and thus seems to be linked to low aggressiveness of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that glucose metabolism on 18 F-FDG PET correlates with the patient's prognosis (31)(32)(33) F-FDG PET showed very low sensitivity and significantly lower accuracy than chest CT. In addition, no lymph node metastasis was present in patients with a solid proportion ≤50% according to Lee et al (34) and Matsuguma et al (35). In this context, 18 F-FDG PET is not recommended for the staging of small, pure GGNs.…”
Section: Role Of Fdg-pet For Detecting Subsolid Nodulesmentioning
confidence: 99%
“…NAKATA et al [19] observed that 87% of GGOs with no or a minimal solid component represented pure BAC, whereas 56-91% of GGOs with a more abundant solid component represented invasive adenocarcinoma. Similarly, in a number of reports by Japanese authors, the likelihood of nodal metastasis was zero for tumours with no or minimal solid component on HRCT, and increased to 27-31% for those with a more evident solid component [19][20][21][22][23][24]. Larger GGOs with a solid component are more likely to be PET-positive, and a high standardised uptake value has been reported to correlate with stromal invasion and lymphatic spread [25].…”
Section: Pulmonary Ground-glass Opacities M Infante Et Almentioning
confidence: 99%